Managing Sunni-Shia Tensions: Socio-Political and Cultural Peacebuilding in Sādah Bā ‘Alawiyyah, Indonesia - Bahar, Moh. Syaeful; Taufiq, Muhammad; Faiz, Muhammad Fauzinudin; Harnadi, Dodik; Syawqi, Abdul Haq (SCAD Independent, 2025)
The Sādah Bā ‘Alawiyyah, as part of the Hadhrami Arab diaspora, has historically contributed to the dissemination of Islam in Indonesia. However, limited scholarly attention has been given to how this community internally manages sectarian differences, particularly between Sunni and Shia members. This study aims to fill this gap by investigating how the Sādah Bā ‘Alawiyyah community in Bondowoso navigates Sunni–Shia tensions through everyday peacebuilding practices. Employing a qualitative grounded theory approach, data were collected via in-depth interviews, participant observation, and document analysis. The study explores three key issues: the structural dynamics of the Hadhrami Arab community in Bondowoso, the interactional patterns between Sunni and Shia Sadah in daily life, and the socio-cultural mechanisms that prevent conflict escalation. Findings reveal that historical memory, intergenerational kinship ties, and ritual continuity function as core resources for building trust and sustaining peaceful coexistence. Rather than relying on formal institutions, the community resolves tensions through informal, everyday strategies that foster mutual respect and cohesion. Conceptually, the study contributes to diaspora and peace studies by introducing the notion of “family-based everyday peace”, demonstrating that Hadhrami identity is negotiated not merely through religious authority or social status, but through practical, lived strategies for conflict mitigation within plural settings.